1999
DOI: 10.1007/s11745-999-0416-2
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐dependent inhibition of cell proliferation induced by lipid peroxidation products in rat hepatoma cells after enrichment with arachidonic acid

Abstract: Polyunsaturated fatty acids (PUFA) are important constituents of membrane phospholipids, whose levels are decreased in some tumor cells. This deficiency may cause alterations in signal transduction and an interruption of normal cellular events. The enrichment of tumor cells with PUFA may stimulate or inhibit tumor growth, probably depending on the type of PUFA and the cellular concentration of aldehydes derived from restored lipid peroxidation. We examined the effect of several doses of prooxidant on the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Our finding of noticeable anti-proliferative effect exhibited by ALA and LA treatment, concurs with literature [Lima et al, 2002], suggesting that ALAand LA-induced toxicity is mainly responsible for butterfat-induced antiproliferative effects. Moreover, we found that ALA and LA are mostly responsible for prooxidant-induced antiproliferative effect, which is further supported by data indicating the close relationship between oxidative stress with growth inhibitory effect [Hammer et al, 1997] and 3 H-thymidine incorporation [Muzio et al, 1999]. However, in our study OBF-mediated growth inhibition is not merely the consequence of induced cytotoxicity.…”
Section: Discussionsupporting
confidence: 90%
“…Our finding of noticeable anti-proliferative effect exhibited by ALA and LA treatment, concurs with literature [Lima et al, 2002], suggesting that ALAand LA-induced toxicity is mainly responsible for butterfat-induced antiproliferative effects. Moreover, we found that ALA and LA are mostly responsible for prooxidant-induced antiproliferative effect, which is further supported by data indicating the close relationship between oxidative stress with growth inhibitory effect [Hammer et al, 1997] and 3 H-thymidine incorporation [Muzio et al, 1999]. However, in our study OBF-mediated growth inhibition is not merely the consequence of induced cytotoxicity.…”
Section: Discussionsupporting
confidence: 90%
“…Lipid peroxidation was estimated by determination of the MDA concentration by the thiobarbiturate assay, as described by others (8,16). Briefly, a 0.1-ml aliquot of each sample was mixed with 0.9 ml of trichloroacetic acid (20%; Merck), and the mixture was centrifuged at 12,000 ϫ g and 4°C for 10 min.…”
Section: Animalsmentioning
confidence: 99%
“…Lipid peroxidation in serum was assessed by estimation of the concentration of malondialdehyde according to the thiobarbiturate assay, as described by others [4,5]. Briefly, a 0.1 ml aliquot of each sample was mixed with 0.9 ml of trichloroacetic acid 20% (Merck, Darmstadt, Germany) and centrifuged at 12,000 × g for 10 min at 4 • C. The supernatant was incubated with 1 ml of PBS (Merck) and 1 ml of thiobarbituric acid 0.6% (Merck) for 20 min at 90 • C. Optical density was then read at 535 nm (Hitachi Spectophotometer).…”
Section: Assay For Mda and Tnfαmentioning
confidence: 99%